MAKNA DAMAI SEJAHTERA KRISTUS BERDASARKAN FILIPI 4: 6-7 SEBAGAI DASAR KEHIDUPAN ORANG PERCAYA - Ebelia Jaqcline Septin Pabetteng; Yensi Tangkelangan; Lee Jhines (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the meaning of the peace of Christ based on Philippians 4:6–7 and to explain its relevance as a foundation for the believer's life. The research employs a qualitative method using a library research approach, specifically through an exegetical analysis of the text of Philippians 4:6–7. Data were obtained from the Bible as the primary source and supported by relevant theological books, biblical commentaries, and scholarly journal articles as secondary sources. The findings indicate that the peace of Christ is a gift from God bestowed upon believers who live in fellowship with Christ through prayer, supplication, and thanksgiving. This peace does not depend on life's circumstances; rather, it is a work of God that guards the hearts and minds of believers amidst various challenges. Beyond its theological dimension, the peace of Christ has practical implications for shaping character, strengthening faith, overcoming anxiety, and building a God-centered life. Thus, Philippians 4:6–7 affirms that the peace of Christ serves as a solid foundation for the believer's life, enabling them to face life's dynamics with faith, maturity, and hope.